Hepatitis prevention project in the Korean American community in Killeen, Texas - Hasan, Syed S. (Proc (Bayl Univ Med Cent), 2015)
Educational efforts related to viral hepatitis have the potential to increase awareness and identify chronically infected individuals and can lead to successful vaccination strategies. However, in underserved semirural communities, such as the Korean American community in Killeen, Texas, these outreach activities are lacking. The GanYum (“hepatitis” in Korean) Prevention Project aimed to evaluate thoughts/behaviors, assess vulnerability, and educate Korean Americans on hepatitis B and C. Two outreach events were held at a Korean church and a Korean market (O'Mart) to provide education, screening, and outreach about viral hepatitis. Ninety-six patients were screened at two events. Five patients were found to be positive for hepatitis B surface antigen and were referred to their primary care physicians and the liver clinic at Scott & White Healthcare in Temple, Texas. Fifty-one patients (53%) were found to be immune to hepatitis B, and 40 patients (42%) were hepatitis B vulnerable. We demonstrated that the prevalence of chronic hepatitis B in Koreans in our study is similar to the previously documented prevalence (5%). Our educational efforts were successful in changing perceptions regarding the modes of transmission and exacerbating factors of chronic viral hepatitis and encouraged participants to seek care for their liver diseases, if needed. We found that both venues (the church and Korean market) were appropriate to screen and educate participants; churches seemed to have a more engaged audience.